AB0392 Safety and Tolerability of Iguratimod in Rheumatoid Arthritis with Comorbid Illnesses. (15th July 2016) - Takasugi, K.; Okada, M.; Min, C.; Kitada, A.; Kataoka, Y.; Kaneshita, S.; Suda, M.; Ohara, Y.; Rokutanda, R.; Shimizu, H.; Tsuda, T.; Yamaguchi, K.; et al.
Abstract : Background: Iguratimod, a member of the family of methanesulfonanilide, is a relatively new oral anti-rheumatic medication. Although most of the members of this family act as cyclooxygenase 2 inhibitor, iguratimod has been considered to be a novel immunomodulator agent. Little data exists regarding its safety and tolerability in patients with comorbid illnesses. Objectives: To determine the safety and retention rate of Iguratimod in high risk patients. Methods: For the period from December 2012 to July 2015, a retrospective review of medical records was performed at our institution for all patients who had been treated with Iguratimod for rheumatoid arthritis (RA). Baseline characteristic and clinical course were reviewed. For the analysis, using Kaplan-Meier curves, a comparison of adverse events and the number of treatment switches by each risk category (history of malignant neoplasms, latent tuberculosis infection (LTBI), underlying pulmonary disease, and estimated glomerular filtration rate (eGFR <60 mL/min/1.73m 2 )) was conducted. Results: A total of 173 patients were included in this study. The mean age was 68.7 yrs, and the disease duration was 12±10 yrs. Positivity of ACPA was 79% (the mean titer was 127.3 U/mL). Thirty nine patients (22.5%) have history of neoplasms (over 5 years before: n=13, within 5 years: n=14, on current treatment or on best supportive care (BSC): n=12). Thirty eight patients (22%) have LTBI, 46 patients have underlying pulmonary disease (Interstitial pneumonia: n=30, others: n=16). Estimated eGFR<60ml/min were seen in 28 patient. Adverse effects (AE) include rash (n=4), gastrointestinal symptoms (n=10), liver function test abnormality (n=12), renal impairment (n=9), and interstitial pneumoniae (n=3). None of the patients developed tuberculosis or HBV reactivation during the follow-up period. During the study period, 8 out of the 12 patients with current neoplasms were able to continue Iguratimod. Three patients who currently had neoplasms died during the study (all of whom were BSC patients at the baseline, and the follow-up periods were 199, 378, and 610 days, respectively). One patient was taken off Iguratimod due to an abnormality in the liver function test. There was no statistical significance on the log-rank analysis for AE, and the number of treatment switches was LTBI (p=0.183), neoplasms (p=0.185), underlying pulmonary disease (p=0.136), and eGFR <60ml/min (p=0.373). For AE, LTBI (p=0.239), neoplasms (p=0.953), underlying pulmonary disease (p=0.158), and eGFR <60ml/min (p=0.322). Conclusions: This study demonstrated the safety and tolerability of Iguratimod for established high-risk RA patients. References: Lu LJ, et al. Multicenter, randomized, double-blind, controlled trial of treatment of active rheumatoid arthritis with T-614 compared with methotrexate. Arthritis Care & Research 2009; 61 979–987 Hara M, et al. Safety and efficacy of combinaion therapy of iguratimod with methotrexate for patients with active rheumatoid arthritis with an inadequate responce to methtrecate: An open label extension of a randomized, double-blind, placebo-controlled trial. Modern rheumatology 2014; 24: 410–418. Disclosure of Interest: None declared